Toll-Like Receptor 4 Signaling and Drug Addiction - Wu, Ruyan; Li, Jun-Xu (Frontiers in Pharmacology, 2020)
The emphasis of neuronal alterations and adaptations have long been the main focus of the studies of the mechanistic underpinnings of drug addiction. Recent studies have begun to appreciate the role of innate immune system, especially toll-like receptor 4 (TLR4) in drug reward-associated behaviors and physiology. Drugs like opioids, alcohol and psychostimulants activate TLR4 signaling and subsequently induce proinflammatory responses, which in turn contributes to the development of drug addiction. Inhibition of TLR4 or its downstream effectors attenuated the reinforcing effects of opioids, alcohol and psychostimulants, and this effect is also involved in the withdrawal and relapse-like behaviors of different drug classes. However, conflicting results also argue that TLR4-reltated immune response may play a minimal part in drug addiction. This review discussed the preclinical evidence that whether TLR4 is involved in multiple drug classes action and the possible mechanisms underlying this effect. Moreover, clinical studies which examined the potential efficacy of immune-base pharmacotherapies in treating drug addiction are also discussed.